Pengelolaan Cecingkreman pada Dadia Pasek Gelgel Tabang Desa Bebetin - Purnama, Luh Weda Laksmi; Atmadja, Anantawikrama Tungga (Jurnal Ilmiah Akuntansi dan Humanika, 2020)
This study aimed to determine: (1) the background of the formation of cecingkreman on Dadia Pasek Gelgel Tabang Desa Bebetin, and (2) the mechanism of the management of cecingkreman systems in Dadia Pasek Gelgel Tabang Desa Bebetin. This study was qualitative research with ethnography type. Data collection techniques were done by conducting observation, interviews, and also study documentation. The object of this research was the management of cecingkreman in Dadia Pasek Gelgel Tabang Desa Bebetin. The result show that (1) the background of the formation of cecingkreman is as a means to help the Dadia Pasek Gelgel Tabang society in fullfiling their needs and also as means to maintain solidarity in Dadia Pasek Gelgel Tabang Desa Bebetin, (2) The mechanism of the cecingkreman management system that is owns by Dadia Pasek Gelgel Tabang Desa Bebetin carried out in four stages namely planning, implementation, administration, and also accountability